Bago lumamig ang kape: A documentary - Cerezo, Jana Mikaela A. (Animo Repository, 2023)
Taken from the perspective of a university student, Bago Lumamig Ang Kape is a short documentary film that spotlights the emotional aftermath of the horrifying Philippine war on drugs. It primarily focuses on the lives of the families left behind by the victims of the drug war, who found solace and healing through Silingan Coffee – a coffee shop in the heart of Quezon City. It centers on three middle-aged female baristas who all lost immediate family members and are now working at Silingan Coffee. The aforementioned employees provide a brief background on their experiences, discuss how they are handling the various stages of their mourning processes, and express how working at Silingan Coffee helps them deal with their losses. The purpose of the short documentary film is to show that life does not have to end after grief; there are hopeful ways to learn how to cope with these experiences. The proponent carefully considered the required ethical precautions when filming in order to respect the subjects' integrity and dignity given the sensitivity and nature of the events that have occurred. 1080p. MP4 Format.